A Wheel Chair Prototype Moved by means of Eye Blinks - Morín-Castillo, M. M.; Santillán-Guzmán, A.; Sainos González, S. L.; Oliveros-Oliveros, J. J. (Revista Mexicana de Ingenieria Biomedica, 2018)
The present work describes a prototype of a wheel chair directed by means of eye blinks, which can be moved forwards, and backwards using 2 or 3 eye blinks, respectively, and stopped when a certain attention level is met. The main objective of this work is to help people, who have motor disabilities on their arms and legs, move and have autonomy. In order to register the eye blinking signals, the MindWave Mobile device from Neurosky was used. Moreover, an electronic circuit in combination with Arduino has been used to make the prototype work. This pro-totype has been tested in 10 healthy people from 20 to 35 years old. According to the results, in 80% of the cases the prototype worked correctly. The main advantage of the present work is that the brain-computer interface, which is part of the prototype, does not require training, and hence, it could be used by most of the people. Moreover, its cost is less than similar devices.